Microduplications at the pseudoautosomal SHOX locus in autism spectrum disorders and related neurodevelopmental conditions. Issue 8 (12th April 2016) - Tropeano, Maria; Howley, Deirdre; Gazzellone, Matthew J; Wilson, C Ellie; Ahn, Joo Wook; Stavropoulos, Dimitri J; Murphy, Clodagh M; Eis, Peggy S; Hatchwell, Eli; Dobson, Richard J B; Robertson, Dene; Holder, Muriel; et al.
Abstract : Background: The pseudoautosomal short stature homeobox-containing ( SHOX ) gene encodes a homeodomain transcription factor involved in cell-cycle and growth regulation. SHOX / SHOX enhancers deletions cause short stature and skeletal abnormalities in a female-dominant fashion; duplications appear to be rare. Neurodevelopmental disorders (NDDs), such as autism spectrum disorders (ASDs), are complex disorders with high heritability and skewed sex ratio; several rare (<1% frequency) CNVs have been implicated in risk. Methods: We analysed data from a discovery series of 90 adult ASD cases, who underwent clinical genetic testing by array-comparative genomic hybridisation (CGH). Twenty-seven individuals harboured CNV abnormalities, including two unrelated females with microduplications affecting SHOX . To determine the prevalence of SHOX duplications and delineate their associated phenotypic spectrum, we subsequently examined array-CGH data from a follow-up sample of 26 574 patients, including 18 857 with NDD (3541 with ASD). Results: We found a significant enrichment of SHOX microduplications in the NDD cases (p=0.00036; OR 2.21) and, particularly, in those with ASD (p=9.18×10 −7 ; OR 3.63) compared with 12 594 population-based controls. SHOX duplications affecting the upstream or downstream enhancers were enriched only in females with NDD (p=0.0043; OR 2.69/p=0.00020; OR 7.20), but not in males (p=0.404; OR 1.38/p=0.096; OR 2.21). Conclusions: Microduplications at the SHOX locus are a low penetrance risk factor for ASD/NDD, with increased risk in both sexes. However, a concomitant duplication of SHOX enhancers may be required to trigger a NDD in females. Since specific SHOX isoforms are exclusively expressed in the developing foetal brain, this may reflect the pathogenic effect of altered SHOX protein dosage on neurodevelopment.